Transition From Primary to Secondary School Through Visual Arts Education (LEARNing Landscapes, 2016)
Moving from primary to secondary school is a major challenge. This article presents the concept of educational transition, makes a case for its relationship with identity formation, and discusses its e ects on students’ academic achievement, social adjustment, and self-concepts. It explores the role of art and creativity to foster resilience and presents an example of how visual arts were used to help students negotiate and reframe transition. It concludes with further practical considerations for art education with the hope that visual arts can play a critical role in ensuring that students successfully meet the challenges along the way to secondary school.
Keywords: eductional transition; identity; academic acheivement; social adjustment; art; visual arts